(untitled) (Bangladesh Journal of Medical Science, 2021)
Objective:Averrhoa bilimbi fruit contains potassium and flavonoid expected to play a role in lowering blood pressure. This study aim to examine the effect of Averrhoa bilimbi fruit extract on blood pressure and mean arterial pressure in NaCl-induced hypertensive rats. Materials and methods: This research employs pre- and post-test randomized control group design and uses 15 rats which are divided into 3 groups. On day 6, all groups are pretreated with NaCl 8% solution to induce hypertension for 14 days. On day 20, the control, furosemide and bilimbi groups are respectively treated with distilled water, 0.72mg/200gBW furosemide, and 150mg/200gBW Averrhoa bilimbi fruit extract for 7 days. The (systolic and diastolic) blood pressure and mean arterial pressure of each group are evaluated on day 20 and 27. The results are analyzed with Repeated Anova. Results: The mean systolic and diastolic blood pressure of the control, furosemide and bilimbi group before treatment are (128.4±11.8/88.0±7.8mmHg); (142.8±13.6/85.4±16.7mmHg); and (144.8±15.1/98.0±14.9mmHg) respectively. The mean systolic and diastolic blood pressure of the control, furosemide and bilimbi group after being treated are (88.0±11.8/60.8±7.8mmHg); (98.0±13.6/71.0±16.7mmHg); and (85.4±15.1/65.0±14.9mmHg) respectively. The mean arterial pressure of the control, furosemide and bilimbi groups are (69.4±8.2mmHg); (79.6±14.8mmHg); (71.4±15.0mmHg) respectively. There is a statistically significant difference in the blood pressure and the mean arterial pressure among the groups (p=0.000). Averrhoa bilimbi fruit extract has an effect on the blood pressure and the mean arterial pressure of NaCl-induced hypertensive rats. Bangladesh Journal of Medical Science Vol.20(3) 2021 p.631-636